1998
DOI: 10.1051/aas:1998314
|View full text |Cite
|
Sign up to set email alerts
|

The infrared and optical variability of OJ 287

Abstract: Abstract. In this paper, the long-term historical optical (UBV RI) and near-infrared (JHK) data are presented with some new observations in the optical (February 1994-January 1995 m 87; ∆H = 3. m 78; ∆K = 3. m 54. A strong correlation is found between the optical and near-infrared bands when the DCF method is used, which suggests that these two bands have the same emission mechanism.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…The scatter in the B − V index increased when the object became fainter than 14. m 5. A close correlation between the B − V color index and the V magnitude was found by Fan et al (1998) based on a dozen points obtained in winter 1994-95, at the falling branch of brightness after the maximum in 1994.…”
Section: Color Variationssupporting
confidence: 60%
“…The scatter in the B − V index increased when the object became fainter than 14. m 5. A close correlation between the B − V color index and the V magnitude was found by Fan et al (1998) based on a dozen points obtained in winter 1994-95, at the falling branch of brightness after the maximum in 1994.…”
Section: Color Variationssupporting
confidence: 60%
“…No significant negative correlation was found for any BL Lac which reflects the common trend for this class that they become bluer when they brighten (Ghisellini et al 1997;Fan et al 1998;Massaro et al 1998;Fan & Lin 1999;Ghosh et al 2000;Raiteri et al 2001;Villata et al 2002;Gu et al 2006;Rani et al 2010a). It has been found that the amplitude of the variations is systematically larger at higher frequencies, which suggests that the spectrum becomes steeper when the source brightness decreases, and flatter when it increases (Ghisellini et al 1997;Massaro et al 1998).…”
Section: Relation Between Colour Index and Flux Variationmentioning
confidence: 87%
“…BL Lac has been studied in detail during various intensive multiwavelength campaigns (Madejski et al 1999;Villata et al 2002;Böttcher et al 2003;Ravasio et al 2003 and references therein). Fan et al (1998) presented historical optical data (in UBVRI) over ∼100 yr covering the period 1896-1996 and found large variations in all the bands.…”
Section: Bl Lacmentioning
confidence: 99%
“…2, 9 and 12) observed during the latest outbursts show clearly that during the first optical flare the radio bands showed minimum flux (see Valtaoja et al 2000). Figure 2 shows the observed optical light curves, displaying clearly the outbursts in November 1994 and end of December 1995 (Arimoto et al 1997;Fan et al 1998b;Kidger et al 1995;Sillanpää et al 1996a,b). The separation between these two outbursts is 1.1 years (Sillanpää et al 1996b;, which is very similar to the one observed in 1972/73 and 1983/84 (Sillanpää et al 1988).…”
Section: Resultsmentioning
confidence: 89%
“…The project archive contains also the data published by Arimoto et al (1997), Fan et al (1998b), Jia et al (1998) and Stevens et al (1994). These data will be also used in the following sections of this article.…”
Section: Fig 3 Example Of the Observed Flaring Activity In Differenmentioning
confidence: 99%